PENGARUH LATIHAN PLIOMETRIK TERHADAP HASIL LONG PASSING SEPAK BOLA - Ahmad Ridwan; Eka Supriatna; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to investigate the significance of plyometric training to the long passing outcome on soccer. Population was taken from rawak football club which consisted of 24 candidates. Technique of data sampling was satu ration sampling. Metode of the research was experimental with one group deseign pre-test. The data were collected with tests and measurement teacnique. The resuld showed that the ability of long passing on football (47,35). The lowest value was (40,3), where as the height value was (56,2). The significance of the value of pre-test and post-test the was <0,05, which implies that the normality test of data is valid. The result of homogeneity showed valid. As the t test was p value 0,018 < 0.05, the alternative hypothesis (ha) is acceped. In conclusion, plyometric training has significant infact to the outcome of long passingin football or rawak football club players.Keywords: plyometric, long passing